ANALISIS PERSEPSI MASYARAKAT TERHADAP TAMAN DI KOTA MAKASSAR - Suhasman Suhasman; Agussalim Agussalim; Nurbani Yusuf (Badan Penelitian dan Pengembangan Daerah Kota Makassar, 2017)
Regulation of the Minister of Public of Works No.05 / PRT / M / 2008 has outlined the form of Green Open Space provision based on the number of people dominated by the type of park, both at the environmental level and at the city level. The park has a social and aesthetic function as a means of recreational, educational and other activities for people. This study aimed to evaluate the condition of the park and public perception of the park in Makassar. The object of this research was the parks in the city of Makassar selected by chance which represents every sub-district in Makassar. Observation of facilities and vegetation conditions was based on Regulation No.5 2008. Furthermore, some the parks' visitors were also selected as samples in this study within the framework of observing people's perceptions. Instruments used in this study was a questionnaire that contains some questions that are closed or open. This questionnaire was used in interviewing the parks' visitors. Data obtained was tabulated then analyzed descriptively. Based on the observation result, it is found that the condition of the parks does not have complete facilities, and carries aesthetic function than social and ecological function. The community also said that the parks need to improve in terms of its facilities and vegetation.